The Adducts Lipid Peroxidation Products with 2′-DeoxyNucleosides: A Theoretical Approach of Ionisation Potential - Boleslaw T. Karwowski (Applied Sciences)
The human body contains ~1014 cells—each of which is separated by a lipid bilayer, along with its organeller. Unsaturated fatty acids are located on the external layer and, as a result, are particularly exposed to harmful factors, including xenobiotics and ionising radiation. During this activity, lipid peroxidation products are generated, e.g., 4-hydroxy-2-nonenal (HNA), 4-oxo-2(E)-nonenal (ONE), and malondialdehyde (MDA). The mentioned aldehydes can react with cytosolic 2′-deoxynucleosides via Michael addition. In this paper, the following adducts have been taken into theoretical consideration: ε-dCyt, H-ε-dAde, ε-dCyt, H-ε-dAde, H-ε-dGua, R/S-OH-PdGua, N2,3-ε-dGua, M1-dGua, N1-ε-dGua, and HNE-dGua. The presence of the above molecules can alter a cell’s antioxidant pool. With this in mind, the adiabatic ionisation potential (AIP) and vertical ionisation potential (VIP), as well as the spin and charge distributions, are discussed. For this purpose, DFT studies were performed at the M06-2x/6-31++G** level of theory in the aqueous phase (both non-equilibrated (NE) and equilibrated (EQ) solvent–solute interaction modes), together with a Hirshfeld charge and spin distribution analysis. The obtained results indicate that the AIPs of all the investigated molecules fell within a range of 5.72 and 5.98 eV, which is consistent with the reference value of 7,8-dihydro-8-oxo-2′-deoxyguanosine (OXOdGua), 5.78 eV. N2,3-ε-dGua and M1-dGua were the only exceptions, whose VIP and AIP were noted as higher. The electronic properties analysis of 2′-deoxynucleoside adducts with lipid peroxidation products reveals their potential influence on the cells’ antioxidant pool, whereby they can affect the communication process between proteins, lipids, and nucleotides.